2018
DOI: 10.1016/j.cam.2017.07.033
|View full text |Cite
|
Sign up to set email alerts
|

A numerical method for pricing discrete double barrier option by Legendre multiwavelet

Abstract: In this paper, a rapid and high accurate numerical method for pricing discrete single and double barrier knock-out call options is presented. According to the well-known Black-Scholes framework, the price of option in each monitoring date could be calculate by computing a recursive integral formula upon the heat equation solution. We have approximated these recursive solutions with the aim of Lagrange interpolation on Jacobi polynomials node. After that, an operational matrix, that makes our computation signif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…It has been extensively used by options traders and is known to result in considerable growth in options trading due to its effectiveness and accuracy in predicting the options prices. More recently, some techniques have been proposed for numerically approximating the B-S model such as Farnoosh et al (2015Farnoosh et al ( , 2016Farnoosh et al ( , 2017, Golbabai and Mohebianfar (2017a, b), Golbabai et al (2012Golbabai et al ( , 2014, Rad et al (2015), Rashidinia and Jamalzadeh (2017a, b), and Sobhani and Milev (2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively used by options traders and is known to result in considerable growth in options trading due to its effectiveness and accuracy in predicting the options prices. More recently, some techniques have been proposed for numerically approximating the B-S model such as Farnoosh et al (2015Farnoosh et al ( , 2016Farnoosh et al ( , 2017, Golbabai and Mohebianfar (2017a, b), Golbabai et al (2012Golbabai et al ( , 2014, Rad et al (2015), Rashidinia and Jamalzadeh (2017a, b), and Sobhani and Milev (2018).…”
Section: Introductionmentioning
confidence: 99%
“…e most famous PDE in finance is the Black-Scholes (B-S) model, which is broadly adopted for option pricing. So far, studies have presented different approaches for finding the numerical solution of this model and its variation when the exact form does not exist [5][6][7][8][9][10][11][12][13]. By using tick-by-tick data, Cartea and del-Castillo-Negrete [14] found that the value of European-style options satisfies a FPDE containing a nonlocal operator in time-to-maturity known as the Caputo fractional derivative.…”
Section: Introductionmentioning
confidence: 99%
“…The most famous PDE in finance is the Black-Scholes (B-S) model, which is broadly adopted for option pricing. So far, studies have presented different approaches for finding numerical solution of this model and its variation when the exact form does not exist ; Farnoosh (2015Farnoosh ( , 2016Farnoosh ( , 2017; Golbabai (2017a,b); Rashidinia (2017a,b); Sobhani (2018)).…”
Section: Introductionmentioning
confidence: 99%